Towards tailoring basal texture of rolled Mg alloy sheet by recrystallization for high room-temperature formability: A review - T. Nakata; S. Kamado (Journal of Magnesium and Alloys, 2023)
Room-temperature (RT) formability is a key factor to broaden the applications of rolled Mg alloy sheets in the industry. However, rolled Mg alloy sheets generally form strong basal texture, where the (0001) poles align parallel to the normal direction (ND). This hinders the activation of (0001) [112¯0] basal slip, limiting the RT formability. Therefore, texture weakening, i.e., the inclination of the (0001) poles from the ND, plays an important role to improve the RT formability. Recrystallization is crucial to control the textural development in Mg, and currently, the texture weakening is commonly achieved using static recrystallization (SRX). However, the type of slipping and twinning, which are activated during rolling, affect the textural features after SRX. It is also demonstrated that shear bands and preferential grain growth are important factors to tailor the texture during SRX. Indeed, dynamic recrystallization (DRX) easily occurs during rolling in Mg, which also affects the final rolling texture, while the effect of DRX on the textural formation is not extensively studied for the development of RT-formable Mg alloy sheets. Therefore, the effect of these factors on the textural development in rolled Mg is reviewed in this manuscript. Additionally, the ideal microstructure and texture for RT-formable Mg alloy sheets are still controversial. The RT-formability includes stretch forming (biaxial tension), bending (plane strain tension), and deep-drawing. In particular, the stretch forming is commonly used to evaluate the RT-formability of rolled Mg. Although the stretch formability has been improved by recent studies, the further improvement is necessary owing to the relatively low formability of rolled Mg compared with that of rolled Fe and Al. Based on the relationship between the microstructure/texture and stretch formability provided in the literature, the design guidance for high stretch formability is proposed in this review.